THE IMPACTS OF INSTITUTIONAL DISTANCE ON THE LOCATION OF CHINA’s OUTWARD FOREIGN DIRECT INVESTMENT IN ASEAN: An Empirical Research Based on CAGE Distance Framework - Ye, Xue; Don, Mohd Sobri; Alam, A. S. A. Ferdous (International Journal of Global Economics and Management, 2023)
As the world political and economic environment continues to change, the external environment faced by Chinese OFDI enterprises was becoming increasingly complex, with the impacts of institutional distance becoming more prominent.